Muslims in Southern Africa : Johannesburg’s Somali diaspora - (:unkn) unknown (My University, 2019)
"This book presents a socio-historical analysis of the Somali Muslim diaspora in Johannesburg and its impact on urban development in the context of Somali migrations in the Southern African Indian Ocean region from the end of the 19th Century to today. The author draws on a combination of archival and ethnographic research to examine the interlocking processes of migration, urban place-making, economic entrepreneurship and transnational mobility through the lens of religious practice and against the background of historical interactions between the Somali diaspora and the British and Ottoman Empires. Comparison with other Muslim diasporas in the region, primarily Indians, adds further depth to an investigation which will shed new light on the Somali experience of mobility and the urban development of South Africa across its colonial, apartheid and democratic periods. The politics of race, imperial and post-imperial identities, and religious community governance are shown to be key influencing factors on the Somali Diaspora in Johannesburg. This sophisticated analysis will provide a valuable resource for students and scholars of urban geography, the sociology of religion, and African, race, ethnic and migration studies."
Keywords: African Research